2014
DOI: 10.3389/fpsyg.2014.01126
|View full text |Cite
|
Sign up to set email alerts
|

Hypnoanalgesia and the study of pain experience: from Cajal to modern neuroscience

Abstract: Santiago Ramón y Cajal (1852–1934) did not only contribute to neurobiology and neurohistology. At the end of the 19th century, he published one of the first clinical reports on the employment of hypnotic suggestion to induce analgesia (hypnoanalgesia) in order to relieve pain in childbirth. Today, the clinical application of hypnoanalgesia is considered an effective technique for the treatment of pain in medicine, dentistry, and psychology. However, the knowledge we have today on the neural and cognitive under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 53 publications
0
10
0
3
Order By: Relevance
“…Adicionalmente, se dan cambios a nivel de la conciencia que incluyen el reposo mental, el estar absorto, la reducción de la autoorientación y la automaticidad (Vanhaudenhuysea et al, 2014). Incluso, se han evidenciado procesos de tipo neurofisiológico frente a estos cambios, a la vez que se han comenzado a describir algunos mecanismos cerebrales implicados (Jensen & Patterson, 2014;Lanfranco, Canales-Johnson & Huepe, 2014).…”
Section: Introductionunclassified
See 2 more Smart Citations
“…Adicionalmente, se dan cambios a nivel de la conciencia que incluyen el reposo mental, el estar absorto, la reducción de la autoorientación y la automaticidad (Vanhaudenhuysea et al, 2014). Incluso, se han evidenciado procesos de tipo neurofisiológico frente a estos cambios, a la vez que se han comenzado a describir algunos mecanismos cerebrales implicados (Jensen & Patterson, 2014;Lanfranco, Canales-Johnson & Huepe, 2014).…”
Section: Introductionunclassified
“…La hipnosis clínica es aplicada en diferentes problemáticas, como el dolor (agudo y crónico), la ansiedad, el tabaquismo, los trastornos de estrés postraumático, los trastornos gastrointestinales y otros problemas de salud (Jensen & Patterson, 2014;Landolt & Milling, 2011;Lanfranco et al, 2014;Lynn & Kirsch, 2005;Mendoza & Capafons, 2009;Palsson, 2015). Gracias a la evidencia empírica y a una cuidadosa observación clínica, se ha logrado debatir una serie de mitos, llegando a un consenso científico sobre algunas características de la hipnosis, entre las que se encuentran las siguientes: la hipnosis no es un estado de sueño; bajo hipnosis las personas tienen la capacidad de controlar sus conductas y son conscientes de su entorno; no implica ningún peligro si es realizada por profesionales cualificados; la amnesia poshipnótica es poco frecuente y usualmente reversible cuando ocurre; la hipnosis podría provocar falsos recuerdos, tal como ocurre en el estado de vigilia (Capafons, 1998).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…DCD is associated with greater activation in frontal, parietal, and temporal brain regions but reduced activation of areas associated with motor control, motor learning, and error processing, and is considered a consequence of delayed cerebellar development [2,26,28]. Although basal ganglia and parietal cortex alterations could play a role in DCD [26], they may exert it through their connections with the cerebellum [32,33].…”
Section: Discussionmentioning
confidence: 98%
“…This ability, which is widely used to control pain [2], has been classically attributed to peculiar attentional characteristics sustained by a more efficient executive control [3]. In contrast, more recent evidence have shown that the higher ability of highly hypnotizable people (highs) to keep their attention focused on a selected object should be interpreted as a reduced capacity to redirect attention from its current focus toward a new object [4,5].…”
Section: Introductionmentioning
confidence: 97%